2020
DOI: 10.1002/fes3.223
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of leaf properties and plant phenotype through yield‐based genetic improvement of rice over a period of seventy years in the Yangtze River Basin of China

Abstract: Knowledge of changes associated with the progression of growth‐related characteristics in rice plant is essential to make strategies for future breeding and crop management. However, thus far, little attention has been given to the identification of temporal changes of the traits concomitant with the year of release in rice genetic breeding. The objective of this study was to explore genetic gain for yield accrued in association with evolution of the growth phenotypes in a 2‐year field experiment conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
(68 reference statements)
2
16
0
Order By: Relevance
“…The gradient of light in the canopy can be described by the parameter K L ; a smaller K L indicates a better light distribution (Gu, Chen, et al, 2017). Our results showed that the application of N or K reduced the K L ; the reason may be that the fertilization influenced the canopy structure (such as leaf area, relative height, leaf angle, and height difference of adjacent leaves) and then improved light distribution (Song et al, 2013; Zhu et al, 2020). Similarly, it was observed that cultivars with more erect leaves in the upper canopy allowed more light to reach the lower layers, resulting in higher light use efficiency (Long et al, 2006; Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The gradient of light in the canopy can be described by the parameter K L ; a smaller K L indicates a better light distribution (Gu, Chen, et al, 2017). Our results showed that the application of N or K reduced the K L ; the reason may be that the fertilization influenced the canopy structure (such as leaf area, relative height, leaf angle, and height difference of adjacent leaves) and then improved light distribution (Song et al, 2013; Zhu et al, 2020). Similarly, it was observed that cultivars with more erect leaves in the upper canopy allowed more light to reach the lower layers, resulting in higher light use efficiency (Long et al, 2006; Zhu et al, 2020).…”
Section: Discussionmentioning
confidence: 72%
“…Our results showed that the application of N or K reduced the K L ; the reason may be that the fertilization influenced the canopy structure (such as leaf area, relative height, leaf angle, and height difference of adjacent leaves) and then improved light distribution (Song et al, 2013;Zhu et al, 2020). Similarly, it was observed that cultivars with more erect leaves in the upper canopy allowed more light to reach the lower layers, resulting in higher light use efficiency (Long et al, 2006;Zhu et al, 2020). In addition, rice with reduced chlorophyll content may improve canopy light distribution and the photosynthetic rate .…”
Section: Discussionmentioning
confidence: 75%
“…Genetic improvement is a determinant factor for increased yields across many ricegrowing countries, such as India, Japan, the Philippines, and Thailand [6][7][8][9][10]. In China, genetic progress in rice grain yield was reported in the northeast [11,12], southwest [13], south [14], and central China [15,16]. Such studies suggested that genetic progress greatly increased rice grain yield, which was associated with prolonged growth period [6,14], expanded sink size through spikelets per panicle [12,15], and increased biomass accumulation, harvest index, or both [9,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…Canopies consisting of plants with upright leaf angles allow for penetration of radiation to the lower canopy layers, resulting in a more homogeneous light distribution over canopy layers and therefore higher canopy photosynthesis (Marchiori et al, 2010;Sarlikioti et al, 2011). This better distribution of radiation within the canopy is usually associated with low light extinction coefficient and high biomass (Zhu et al, 2020). For crucifers, the horizontal leaf orientation leads to a high capture of radiation in the top layers of the canopy, resulting in light saturation and comparatively inefficient conversion of light into assimilates.…”
Section: Cover Crop Species In Pure Standmentioning
confidence: 99%
“…At the same time, this also leads to more shading of the lower layers of the canopy, and a poor contribution of the lower layers to overall canopy photosynthesis. The higher light extinction coefficient and better radiation interception is thus associated with a relatively low RUE (Zhu et al, 2020).…”
Section: Cover Crop Species In Pure Standmentioning
confidence: 99%